Implicit 3D geological modeling method based on expert knowledge constraints: A case study from the Songshugang Mining District, Hengfeng County, Jiangxi Province, China - Wenlong Jin; Zhichun Wu; Zhe Xu; Hongda Li; Bin Li; Fusheng Guo; Zhiqiang Zhang; Fenling Ma; Hualiang Li; Peng Lu (PLoS ONE, 2026)
Implicit 3D geological modeling offers advantages in rapid model construction; however, purely data-driven approaches have limitations in modeling accuracy and often fail to represent complex geological structures faithfully. To enhance the accuracy and applicability of implicit 3D geological modeling, a method that integrates data-driven approaches with expert knowledge constraints is proposed. Using Leapfrog Geo as the platform, this study integrated multi-source data (boreholes, exploration line profiles) with geological expertise and a priori constraints, to achieve a high-precision reconstruction of the complex geological structure and 3D grade distribution in the Songshugang Ta-Nb deposit, Hengfeng, Jiangxi. Subsequently, deep-seated mineralization targets were predicted. The results demonstrate that this method significantly enhances the modeling accuracy and efficiency for intricate geological bodies. The constructed three-dimensional geological model indicates that the mineralization enrichment zones are located at the contact zones between sodic feldspar granite and the overlying potassic feldspar granite and greisenized granite, as well as between sodic feldspar granite and the underlying biotite granite. Based on this, two favorable mineral exploration targets have been predicted in the deeper regions.